STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT LEGENDA BATU BANGKAI DI KANAGARIAN ALAM PAUAH DUO KECAMATAN PAUAH DUO KABUPATEN SOLOK SELATAN - Wahyuli, Indri; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2019)
The study aims to describe: (1) the structure of local legend Batu Bangkai in Kanagarian Alama Pauah Duo Sub-district Pauah Duo District Solok Selatan, and (2) the social function of local legend Batu Bangkai in Kanagarian Alama Pauah Duo Sub-district Pauah Duo District Solok Selatan. The source of this research data is story about local legend Batu Bangkai in Kanagarian Alam Pauah Duo Sub-district Pauah Duo District Solok Selatan. Based on result of the study concluded: (1) The folklore the main character of local legend Batu BangkaiÂ is a rebellious child, slot of the story is conventional slot, the story happened in Kanagarian Alama Pauah Duo Sub-district Pauah Duo District Solok Selatan,Â the language told by informant with understoodable language, the massage of the story is to be honest, to help each other, and never give up, and (2) social function of the local legend Batu Bangkai are for entertain, education, and cultural preservation.Â Keywords: folklore, structure, social function